Hadith #2931 - Sunan Abi Dawud - Abdur Rahman bin al-Qasim عبد الرحمن بن القاسم بن محمد بن أبي بكر; Aisha bint Abi Bakr; al-Qasim ibn Muhammad القاسم بن محمد بن أبي بكر الصديق; al-Walid bin Muslim al-Quraishi الوليد بن مسلم القرشي; Musa bin 'Amir bin Amarh موسى بن عامر بن عمارة بن خريم; Zuhayr bin Muhammad al-Tamimi زهير بن محمد التميمي (Sunan Abi Dawud)
The Prophet (ﷺ) appointed Ubn Umm Makthum as a governor of Medina (in his absence) twice.
Grade: Sahih

Hadith #4637 - Sunan Abi Dawud - Abdullah bin al-'Ala' عبد الله بن العلاء بن زبر; al-Walid bin Muslim al-Quraishi الوليد بن مسلم القرشي; Musa bin 'Amir bin Amarh موسى بن عامر بن عمارة بن خريم (Sunan Abi Dawud)
Messenger of Allah (ﷺ)! I saw (in a dream) that a bucket was hung from the sky. Abu Bakr came, caught hold of both ends of its wooden handle, and drank a little of it. Next came ‘Umar who caught hold of both ends of its wooden handle and drank of it to his fill. Next came ‘Uthman who caught hold of both ends of its handle and drank of it to his fill. Next came ‘All. He caught hold of both ends of its handle, but it became upset and some (water) from it was sprinkled on him.
Grade: Hasan